Impact of screening mammography on the identification of predictors of breast cancer in the State of Tocantins (Research, Society and Development, 2021)
Justification and Objective: In the state of Tocantins, an estimated 290 new cases of breast cancer are expected in 2020. Therefore, mammography is the main exam for the screening and diagnosis of breast cancer. The aim of this study was to evaluate the proportion of screening mammography in relation to that of diagnosis in view of the identification of predictive findings for breast cancer in Tocantins. Methods: This is a descriptive analytical research, with a quantitative approach, in which data were searched in the Cancer Information System for the years 2015 to 2019. Results: When statistical tests were applied, it was revealed that there was sufficient evidence at the time level of significance of 5% that there is an association between the results of screening mammograms and diagnoses and reports categorized by BI-RADS. There was a higher prevalence of mammograms reported as category zero. There were more malignancy findings in the diagnostic mammography group. Conclusions: From the present study, it can be seen how important screening mammography was in identifying changes (benign and malignant). Even so, there was a higher prevalence of predictors of malignancy on diagnostic mammography. It should be noted that screening and early diagnosis actions are necessary according to the recommendations of the Ministry of Health, as well as improving the system of reports, so that there is no compromise in the effectiveness of breast cancer screening.